Development of bioanalytical standardization parameters of Alocasia indica tuber by HPTLC technique (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Alocasia indica is perennial herb growing widely and used as traditional medicine in India, China and Bangladesh. The divine herb has potent medicinal values for the treatment of different type of illnesses. The HPTLC techniques were used to separate active components from ethanolic extract of tuber part of A. indica. This examination was intended to designed a HPTLC fingerprint profile of crude extract of the plant in ethanol. A HPTLC method for the isolation of various active constituents in A. indica ethanolic extract have been developed and solvent system for quercetin the mobile phase used was toluene: ethyl acetate: formic acid (5:2:1) and for analysis of β-sitosterol the mobile phase used was chloroform: ethyl acetate: formic acid (6:4:1) . In the present investigation, HPTLC fingerprint of extract of dried tuber part of A. indica have been performed and the results demonstrated that important information for standardization. The HPTLC system for routine quality control of present species can be used for ethanolic extract and serve in qualitative, quantitative and was appropriate for standardization of the plant.